PENGEMBANGAN KURIKULUM BERBASIS ADIWIYATA UNTUK MENINGKATKAN KEMAMPUAN PRACTICAL LIFE - Didit Haryadi; Hendro Widodo (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The low sense of caring for the environment becomes a need that must be met through real learning. Creating awareness and life skills is the best way to create culture. One way that needs to be improved in schools is by synchronizing the curriculum that can be used to improve the ability of practical life in caring and cultured environments. This research aims to develop an adiwiyata-based curriculum in shaping and enhancing the ability of practical life to care and be cultured. The setting of this study is Pangudiluhur Sedayu Junior High School Yogyakarta with the subjects of the principal, teachers, and students. This research method uses qualitative approach using the case study. Data collection techniques used were observation, interviews and documentation. The results of this study indicate that the development of Adiwiyata-based curriculum in SMP Pangudiluhur has a unique characteristic that is the curriculum that is synchronized with adiwiyata to improve the ability of practical life. The findings of the research that has been done are identifying concepts and making new policies related to the adiwiyata program in the school environment. Keywords: Curriculum, Adiwiyata, Practical Life, Care, Cultured